2020
DOI: 10.4103/ijo.ijo_1486_19
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab for iatrogenic choroidal neovascular membrane following vitreoretinal surgery for retinal detachment

Abstract: We report the successful use of intravitreal bevacizumab in the iatrogenic choroidal neovascular membrane (CNVM) following vitreoretinal surgery. A 69-year-old male underwent vitrectomy surgery with silicone oil (SO) tamponade for rhegmatogenous retinal detachment. During fluid air exchange, there was an accidental retinal touch at an area in the papillomacular bundle with the silicone tip cannula. He had persistent subretinal bleed at the area 1 month after surgery. The optical coherence tomography (OCT) show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Efficacy of anti-VEGF antibody preparations and corticosteroids have been described without retinal toxicity. [17][18][19] Animal studies have shown safety with findings supporting clinical practice of using unadjusted dosage of intravitreal antiviral injection and implant. Ganciclovir dosages of up to 200 mcg/0.1 mL were safe for serial intravitreal injection in rabbit eyes filled with silicone oil.…”
Section: Review Of Literature and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Efficacy of anti-VEGF antibody preparations and corticosteroids have been described without retinal toxicity. [17][18][19] Animal studies have shown safety with findings supporting clinical practice of using unadjusted dosage of intravitreal antiviral injection and implant. Ganciclovir dosages of up to 200 mcg/0.1 mL were safe for serial intravitreal injection in rabbit eyes filled with silicone oil.…”
Section: Review Of Literature and Discussionmentioning
confidence: 90%
“…Efficacy of anti-VEGF antibody preparations and corticosteroids have been described without retinal toxicity. 1719…”
Section: Review Of Literature and Discussionmentioning
confidence: 99%
“…growth factor therapy in a silicone oil-filled eye was found to be safe and effective for iris neovascularisation, neovascular glaucoma, myopic choroidal neovascular membrane, and choroidal neovascularization after vitrectomy. [6][7][8][9] In a meta-analysis, a dexamethasone implant was known to increase the anatomical outcomes significantly in patients of diabetic macular edema but was not known to improve the visual acuity, especially in phakic patients due to development of cataract. 10 There has been a case report of the use of dexamethasone implant for recurrent macular edema in a silicone oil-filled eye.…”
Section: Discussionmentioning
confidence: 99%
“…Around 3.2 million people worldwide are suffering from DR [7] . However, conventional anti‐DR therapies, including laser photocoagulation and vitrectomy surgery, are unsatisfactory due to the unavoidable side‐effects [8] . Notably, medicinal herbal treatment exerted positive effects on alleviating DR‐induced complications [9] .…”
Section: Introductionmentioning
confidence: 99%